Unlocking Energy Innovation : How America Can Build a Low-Cost, Low-Carbon Energy System - Lester, Richard K. (Richard Keith), 1954- (Book collections on Project MUSE., 2012)
"The authors outline three waves of energy innovation to reveal how America can speed up the introduction of new technologies and business models and accelerate deployment on a massive scale"--Publisher